Assessment of retinal ganglion cell complex thickness in diabetic patients before and after intravitreal injection ofanti-vegf agents (ranibizumab) by spectral domain O.C.T - Sally Farouk Fathy Elgendy; Ali Mohamed Taha; Khaled Gamal Abualenen; Noha Mahmoud Khalil (Cairo : Sally Farouk Fathy Elgendy, 2017)
Purpose:To evaluate retinal ganglion cell complex thickness before and after Ranibizumab intravitreal injection in patients of diabetic macular edema using spectral domain optical coherence tomography (SD-OCT) scans.Methods : prospective interventional case series ,Thirty- three eyes of 27 patientswith diabetic macular edema were imaged by spectral domain optical coherence tomography (SD-OCT) before receiving Ranibizumabintravitreal injection,4 weeks and 2 months after injection . thickness changes in retinal ganglion cell complex after 3 months follow up period were quantitatively analyzed and correlated. Results:There is a statistical significant decrease in Average Retinal ganglion cell complex thicknessas well as the superior and inferior ganglion cell thickness ( P value <0.001, 0.000 and 0.000 ) respectively. The correlation between ganglion cell complex thickness values and duration of diabetes mellitus shows no statistical significant relation .Conclusion : Intra-vitreal Ranibizumab injection cause significant reduction in the Average, superior,inferior thickness of retinal ganglion cell layer in diabetic patients along 3 months follow up period ,with negative correlation between duration of diabetes and ganglion cell complex thickness parameters.Further studies with larger sample,longer follow-up and greater number of injections ,are warranted
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Ophthalmology
Issued also as CD
Keywords: Diabetic Macular Edema; Intravitreal Ranibizumab Injection; Retina